Pelaksanaan Gerakan Literasi Sekolah di Sekolah Menengah Pertama - Billy Antoro; Endry Boeriswati; Eva Leiliyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to evaluate the implementation of the GLS program at SMP Negeri 107 Jakarta. The method used is descriptive with a mixed approach (qualitative and quantitative). The results showed that: (1) Context evaluation, students, teachers and parents viewed the GLS program as needed by students; (2) input evaluation, the majority of teachers do not have adequate literacy capacity, the School Committee and parents support the GLS program, there is a Literacy Working Group Team and there is no public involvement; (3) Process evaluation, principals, teachers and education staff were involved in the 15 minute reading activity, the majority of teachers had taught the correct reading and summarizing strategies; (4) Product evaluation, the majority of students, teachers and parents feel the benefits of the GLS program, the GLS program affects learning activities, behavior, insights and skills of students. In conclusion, habituation of literacy activities in schools in the form of a 15-minute reading program, plus a literacy-rich physical environment and the use of literacy strategies in learning are proven to be able to form students' new skills. Keywords: CIPP Evaluation, School Literacy Movement, Literacy Program